Questions and answers about islam - Alkhuli, Dr. Muhammad Ali. ([S.l.] : Alfalah House, 1992, 1992)
This invaluable book contains a wide selection of questions and answers about Islam, ranging from the light-hearted to the profound. Dr. Darsh deals in a friendly and practical manner with issues and situations that affect us all today, in a society in which it is not always easy to be a Muslim.